Modelo multicritério de avaliação de desempenho operacional do transporte coletivo por ônibus no município de Fortaleza - Pereira Neto, Waldemiro de Aquino (2001)
The performance evaluation of urban bus companies is considered a difficult task. One of the reasons for that is the variety of aspects to be considered and the involved interests. Such complexity constitutes an obstacle for the structuring of an evaluation model that takes into account the majority of the important aspects. This work presents the development of a multicriteria model for the evaluation of the bus companies that operate the public transport system of Fortaleza. A Multicriteria Decision Aid (MCDA) methodology was chosen for the conception of this model, due to its capacity to aid the structuring and evaluation stages, as well as the ability to deal with objective and subjective aspects of the decision framework. This model identifies the aspects considered important for the companies’ evaluation, according to the judgment of the technicians of ETTUSA (the public company responsible for the management of the Traffic and Transport System of Fortaleza). Through this study, it is intended that the specialists start to notice and comprehend the evaluation process in a constructive way, allowing a more focused analysis of the Bus Transport System and, consequently, a more transparent evaluation of the service offered to the population.